Tremor-Related Quality of Life: A Comparison of Essential Tremor vs. Parkinson’s Disease Patients - Louis, Elan D. (Parkinsonism Relat Disord, 2015)
BACKGROUND: Tremor-related quality of life is a multi-dimensional concept that reflects the physical, emotional and other health effects of tremor. Curiously, tremor-related quality of life has never been directly compared in patients with the two major tremor disorders, essential tremor (ET) and Parkinson’s disease (PD). We performed a head-to-head comparison of ET with PD patients. METHODS: The Quality of Life in Essential Tremor (QUEST) questionnaire was administered to 103 ET and 103 matched PD patients enrolled in a clinical-epidemiological study in New York. RESULTS: The QUEST total score and QUEST physical subscore were higher in ET than PD patients (both p<0.05). In relative terms, ET patients reported significantly more impairment than PD patients in multiple areas; PD patients reported more impairment than ET patients in one area (all p≤0.02). In absolute terms, tremor impacted on many aspects of quality of life in both diseases, including physical and psychosocial, and in one-third or more of PD patients, tremor sometimes, frequently or always interfered with numerous physical activities, including writing, using a typewriter/computer, fixing small things, dressing, eating, and holding reading material. CONCLUSIONS: Tremor is a clinical entity that can have numerous effects on patients. While there were relative differences between the two major tremor disorders, ET and PD, in absolute terms, tremor impacted on several domains of quality of life, from physical to psychosocial, in a large proportion of ET and PD patients. Attempts to judge the efficacy of treatments for tremor, whether pharmacological or surgical, should consider its broad impact.